Early embryonic developmental toxicity of TPhP and CDP: Roles of PPARγ - Jing HUANG; Yunuo ZHAI; Boyang LI; Jing JI; Chuanhai LI; Shixin LIU; Yiman LIU; Junhua YUAN; Qixiao JIANG (环境与职业医学)
BackgroundOrganic phosphate flame retardants are emerging environmental pollutants. While there have been multiple toxicities reported following organic phosphate flame retardants exposure, few studies focus on their potential developmental toxicities. It is necessary to elucidate these developmental toxicological effects and underlying mechanisms to improve risk assessments and better protect sensitive populations. ObjectiveTo evaluate potential developmental toxicities in early chicken embryos following exposure to triphenyl phosphate (TPhP) or cresyl diphenyl phosphate (CDP), to reveal TPhP and CDP’s capabilities to activate peroxisome proliferator-activated receptor γ (PPARγ) in vivo in an established chicken embryo gene reporter system, and to investigate the roles of PPARγ in TPhP/CDP-induced developmental toxicities with lentivirus-mediated in vivo gene silencing. MethodsFirstly, diverse doses of TPhP and CDP were injected into the air sacs of fertilized eggs to assess the development of chicken embryos after 6 d of incubation, and an optimal dose was chosen for subsequent experiments. Subsequently, the report gene system was employed to evaluate the intraembryonic activation of PPARγ by TPhP and CDP. Eventually, PPARγ was silenced using lentivirus, and the embryos were co-treated with TPhP and CDP to further disclose the roles of PPARγ in the observed developmental toxicity. ResultsFollowing developmental exposure to TPhP or CDP, significantly lower chicken embryo weights (normalized with egg weights) were observed in the 6 d embryos (10, 30 mg·kg−1 TPhP and 3, 10, 30 mg·kg−1 CDP), indicating that both chemicals have general developmental toxicities and CDP is more potent. Additionally, exposure to CDP also resulted in remarkably increased sagittal brain area (normalized to embryo weights) and decreased sagittal eye area (normalized to embryo weights) (P<0.05), suggesting that CDP has specific developmental neurotoxicity and ocular toxicity. The PPARγ reporter gene experiment results revealed that rosiglitazone (positive control), TPhP, and CDP all significantly activated PPARγ relative to control (P<0.05). The potency order was rosiglitazone > CDP > TPhP. The lentivirus microinjection successfully achieved in vivo silencing of PPARγ in developing chicken embryos, and the estimated silencing efficacy was approximately 55% according to the real-time quantitative polymerase chain reaction (qRT-PCR) results. The in vivo silencing of PPARγ effectively alleviated TPhP or CDP-induced decrease of embryo weights (P<0.05), as well as CDP-induced increase of brain areas and decrease of eye areas (P<0.05). ConclusionsBoth TPhP and CDP can induce general developmental toxicities in early chicken embryos, and CDP is more potent than TPhP. Meanwhile, CDP can induce specific enlarged brain area and decreased eye area. The observed toxicities are associated with in vivo activation of PPARγ.